The Impact of the Criminalization of HIV Non-Disclosure on the Health and Human Rights of “Black” Communities - Wilson, Ciann (Health Tomorrow: Interdisciplinarity and Internationality, 2013)
The criminalization of HIV non-disclosure has become a hot topic for discussion and debate amongst human rights advocates, HIV/AIDS service providers, and people infected and affected by HIV/AIDS. This paper explores the inherent problems with HIV non-disclosure laws. These laws are ambiguous and pose a serious threat to public health policy and programming by obstructing the fundamental human rights of people infected and affected by HIV/AIDS. Using a human rights framework, this paper explores the impact of non-disclosure laws on the health and rights of African, Caribbean, and Black-Canadian communities and proposes ways to address the shortcomings of HIV non-disclosure laws and inadequate social policies.